PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI (Studi pada Biro Organisasi Sekretariat Daerah Provinsi Jawa Tengah) - Niken Ajeng Prihatini, 15.05.51.0122; Indriyaningrum, Kis (Students' Journal of Economic and Management, 2019)
The purpose of this study was to determine the Effect of Work Discipline, Work Motivation and Transformational Leadership Style on Employee Performance at the Bureau of Organization of the Regional Secretariat of Central Java Province. This type of research uses quantitative research, with a total population of 60 people. The sampling technique uses census techniques, so that all population numbers are sampled, amounting to 60 respondents. Data collection uses a questionnaire with a Likert scale. Data analysis in this study used multiple linear regression models. Data processing is done by SPSS 21 program. Based on the calculation results of SPSS 21 from the t test on work discipline variables obtained significance of 0.472> 0.05, then work discipline does not affect employee performance. Work motivation variables obtained significance of 0,000 <0,05, then work motivation has a positive and significant effect on employee performance, transformational leadership style variables obtained significance of 0,023 <0,05, then transformational leadership style has a positive and significant effect on employee performance.